VARIOUS EFFECTS OF NARCOTIC ANALGESICS ON THE CHANGES IN CYTOKINE ACTIVITIES DURING CARDIAC SURGERY WITH CARDIOPULMONARY BYPASS - R. R. Adzhigaliev; A. E. Bautin; N. N. Ilov; V. V. Pasyuga; D. G. Tarasov (Вестник анестезиологии и реаниматологии)
According to experimental data, morphine possesses certain anti-inflammatory properties, which can reduce the manifestations of system inflammatory response (SIR) after cardiopulmonary bypass. Objective: to investigate the effect of various narcotic analgesics on the activity of some SIR markers during peri-operative period of cardiac surgery with cardiopulmonary bypass. Subjects and methods. During the one-centered randomized prospective study, the changes in the concentration of interleukin-6, (IL-6), interleukin-8 (IL-8) and tumor necrosis factor (TNF) were followed up before cardiopulmonary bypass, and in 1, 3 and 24 hours after it in 60 patients, randomly divided into 2 groups. Patients of Group 1 (n = 30) received anesthesia with phentanyl, those from Group 2 (n = 30) received morphine. The groups did not differ in their clinical and demographic parameters and surgery types, performed in them. Results. The significant increase in the concentration of all inflammatory markers was observed in 1 hour after cardiopulmonary bypass was off, which was the evidence of SIR development. In the Group on morphine, the activity of markers was lower versus the Group on phentanyl. Thus, concentration of IL-6 in 3 hours after cardiopulmonary bypass made 155 (113; 180) versus 178 (102; 236) pg/ml (p = 0.006), IL-8 in 1 hour after cardiopulmonary bypass made 37.4 (25.4; 50.2) versus 52.6 (24; 91.4) pg/ml (p = 0,03), in 1 hour the level of TNF achieved 10.7 (8.6; 15.9) versus 15.7 (11.4; 23.1) pg/ml (p = 0.01), and in 3 hours it made − 9.7 (8.3; 13.8) versus 14.1 (9.6; 18.8) pg/ml (p = 0.04). However, there was no difference in the clinical course parameters between the Groups. Conclusion. The obtained results prove the morphine potential to reduce the expression of pro-inflammatory markers when used during cardiac surgery with cardiopulmonary bypass.